21st CENTURY DIGITAL SKILLS: COMMUNICATION, COLLABORATION, CREATIVITY, CRITICAL THINKING IN PRE-SERVICE PHYSICS TEACHER - Firdaus; Ahmad Khoiri; Nugroho Prasetya Adi; Muhammad Najib Al Adib; Eli Trisnowati; Mila Ariyani (Physics Education Study Program, Faculty of Education and Teacher Training, UNSIQ, 2023)
Information and Communication Technology (ICT) development impacts the need for skills in daily life, education, or work. Everyone needs the 4C skills associated with digital skills. Based on the literature review results, there is not much information about the concept of 4C digital skills. So this research will examine what aspects are needed in 4C digital skills. Another objective of this research is to analyze the 4C digital skills of a pre-service physics teacher. This research uses a literature review and survey methods. The subjects in this study were students of the UNSIQ Physics Education Study Program in the 2022/2023 academic year. There are two collection techniques, namely, literature study and questionnaires. Data from the questionnaire will be analyzed by calculating the percentage of each aspect and then determining the categories divided into five, namely very high, high, medium, low, and very low. The findings in this study are that the 4C skills in a digital context can be divided into 4 (four) aspects: critical thinking digital skills, creative digital skills, collaboration digital skills, communication digital skills. These skills are super skills individuals need to succeed in work and education. The results of a survey by the Department of Physics Education, UNSIQ, found creative digital skills as the lowest aspect with a value of 57.35% (low category). In comparison, collaboration digital skills became the highest aspect with a value of 72.20% (high category). Another aspect, namely critical thinking digital skills (61.66%) and communication digital skills (69.24%), are in the medium category.